BER comparison of different modulation schemes over AWGN and Rayleigh fading channels for MIMO-OFDM system. (2017) - Ajose, Simeon Olumide; Bakare, Rasheed Alade; Imoize, Agbotiname Lucky
In this paper, the performance of MIMO-OFDM technology is presented. The system was modelled using Simulink. Distinct modulation schemes: M-ary phase shift keying (M-PSK) and M-ary quadrature amplitude modulation (M-QAM), were employed and two different transmission channels were considered; additive white Gaussian noise (AWGN) and Rayleigh multipath fading channels. First, an OFDM-only system was modelled after which a MIMO-OFDM system was simulated. The simulation of these systems was done over the two different channels. The results obtained showed that the performance of the OFDM system is better over AWGN channel than Rayleigh fading channel for all the modulation schemes. However, with the addition of OSTBC-based MIMO technology to the OFDM system, all the modulation schemes showed better performance over the Rayleigh fading channel (even better than OFDM system over AWGN channel). MIMO systems with transmit diversity and no diversity was considered. Findings generally revealed that the higher the number of the input and output antennas, the better the performance of the communication system.